Faktor Penyebab Terjadinya Kecelakaan Kerja Pada Area Penambangan Batu Kapur Unit Alat Berat PT. Semen Padang - Rolan Kristiawan; Rijal Abdullah (Journals Mining Engineering : Bina Tambang, 2020)
Abstract. PT. Semen Padang is one of the national cement producers in Indonesia whose marketing areaextends from Sumatra to Kalimantan. Limestone as one of the main raw materials in the process of makingcement is obtained from the mining itself. Limestone mining is conducted by quarry using a benching system,which is a mining system that forms levels that divide the mining area into several fronts and work floors. Basedon preliminary observations the author has made on the mining of PT. Semen Padang did not find violations ofthe SOP. Workers use PPE that has been provided by the company. For 2018 there have been 20 workaccidents at PT. Semen Padang. Work accidents with the classification of minor accidents have the highestnumber of occurrences with 18 occurrences. Meanwhile, work accident with severe classification happened 2times. Based on data obtained from the company, almost all work accidents that occurred at the limestonemining location of PT. Semen Padang is due to low employee knowledge and inadequate communication tools.Estimated occupational accidents at PT. Semen Padang is the existence of rules about Occupational Safetyand Health (K3) that have not been implemented properly.Keywords: K3, Semen Padang, Limestone, SOP, Accidents